Competency level and determinants among infection prevention and control staff in the Middle East and North Africa region - Majid M. Alshamrani; Elias Tannous; Fatmah Othman; Mohammed Al Zunitan; Mohammed Abalkhail; Aiman El-Saed (BMC, 2024)
Abstract Background Competency of the staff working in infection prevention and control (IPC) is the cornerstone of successful IPC programs. The objective was to assess competency level and associated factors among IPC staff working in the Middle East and North Africa (MENA) region. Methods A cross-sectional study was carried out in 2019 among active IPC staff who were members of the Arab Countries Infection Control Network. The questionnaire covered demographic and professional characteristics of IPC staff and characteristics of work facilities and IPC programs. A competency score was created from self-perceived responses to 8 competency domains. The competency score was then transformed into 100-scale and categorized into two groups (≥ median and < median). Results A total of 176 participants completed the survey. Participants were mostly female (65.7%), and the mean age was 40.2 ± 8.3 years. The mean competency score was 61.4%. It was slightly variable between domains, being highest with preventing transmission of infection (65%) and lowest with sterilization and disinfection (59%). Higher (≥ median) competency score was associated with having CBIC certification (p < 0.001). It was also associated with facilities having IPC plan (p = 0.005), IPC committee (p = 0.049), regular meetings of IPC committee (p < 0.001), and IPC plan included communications with healthcare workers (p < 0.001). Domain-specific competency scores were significantly associated with receiving same domain-specific training (p < 0.05 for all). Conclusions The competency levels of IPC staff in the MENA region is still suboptimal. The current finding calls for more regional and national investment in IPC staff by providing up-to-date customized educational and training opportunities.